SUSTAINABILITY ASSESSMENT OF SCHOOL MANAGEMENT INFORMATION SYSTEMS IN ENHANCING THE EFFECTIVENESS AND ACCOUNTABILITY OF EDUCATIONAL GOVERNANCE IN PUBLIC SENIOR HIGH SCHOOLS - Santoso, Lukman (Informatika: Jurnal Teknik Informatika dan Multimedia, 2025)
This study examines the sustainability of the implementation of the School Management Information System (SIMS) in Public Senior High Schools in Indonesia using a mixed methods approach and an explanatory sequential design. The focus of the study is to measure the levels of effectiveness, accountability, as well as the internal and external factors influencing the sustainability of SIMS. Quantitative data were collected through surveys involving at least 100 respondents, while qualitative data was obtained from in-depth interviews and focused group discussions. The results indicate that the sustainability of SIMS is influenced by human resource capacity, school policies, organizational culture, local government support, and technological infrastructure. SIMS has been proven to enhance the effectiveness and accountability of educational management, yet the sustainability of the system requires synergy between technical readiness and consistent policy support. These findings enrich the theory of information system management in the educational context and provide practical implications for policymakers and school administrators in designing sustainable SIMS implementation strategies. The study also identifies limitations related to geographic coverage and observation duration, thus recommending further research with a broader scope and longitudinal approaches to deepen the understanding of SIMS sustainability.